Systematic Literature Review: Implementation of Audio-Visual Media in Primary School Science Learning in 2020-2025 - Umami, Nahdhiatul; Sholeh, Muh; Subali, Bambang; Widiarti, Nuni (Journal of Innovation and Research in Primary Education, 2025)
Audio-visual media integrates sound and visual elements to create content that can be both seen and heard. It is applicable during classroom teaching and learning activities. This literature review aims to examine how audio-visual materials are utilized in Indonesian elementary schools (SD) for teaching natural and social sciences (IPAS). The research employs a Systematic Literature Review (SLR) approach. Data was gathered by identifying articles related to the targeted topic, specifically ten journal articles published between 2020 and 2025 that met the SLR criteria. These articles were sourced from Publish or Perish and Google Scholar. Based on the reviewed articles, it was determined that using audio-visual media in education can strengthen learning effectiveness, enrich students' learning experience, and facilitate understanding of often abstract IPAS concepts. The investigation revealed that audio-visual materials like films, animations, and digital presentations can improve students' comprehension, boost their engagement, and make learning more enjoyable. This study's primary objective is to review previous research on the use of audio-visual materials in IPAS instruction at the primary school levelmaterials in IPAS instruction in primary schools.